Avaliação da função da Interleucina 32γ humana (IL-32γ) durante as infecções aguda e crônica da toxoplasmose em camundongos transgênicos - Queiroz, Jacqueline Pádua de (2018)
Interleukin-32γ is a proinflammatory cytokine produced in response to microorganisms and it seems to be important to control infections in humanscaused by Leishmania (V.) braziliensis, Mycobacterium tuberculosis and HIV. Many studies have been conducted to describe the role or function of IL-32γ in different pathological conditions, including infectious diseases. In the present study, transgenic mice for IL-32γ (IL-32γTG) were used to study the role of this cytokine in Toxoplasma gondii infection. Wild type (WT) and IL-32γTG mice were infected with 10 cysts of ME49 strain, per gavage. Mice were euthanized at day 8 for acute infection analysis and at day 30 for chronic infection analysis. IL-32γTG mice displayed higher morbidity score than WT mice. During acute infection, no significant changes were observed in inflammation score and parasitism load between WT and IL-32γTG mice. However, during chronic infection, the IL-32γ transgenic mice showed high parasitism load being the parasitism increase. Taken together, these results are showing that human interleukin-32γ behave as a critical cytokine during T. gondii chronic infection, as its presence, particularly in the brain, leads to an increase of the parasitism load in this tissue.